Reliability of pterygium redness grading software (PRGS) in describing different types of primary pterygia based on appearance - Mohd Radzi Hilmi,; Mohd Zulfaezal Che Azemin,; Khairidzan Mohd Kamal,; Azrin Esmady Ariffin,; Muhammad Afzam Shah Abdul Rahim,; Mohd Izzuddin Mohd Tamrin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of this study was to evaluate the reliability of Pterygium Redness Grading Software (PRGS) in describing different types of primary pterygia. Ninety-three participants with primary pterygia who visited an ophthalmology clinic were recruited in this study. PRGS is a semi-automated computer program used to measure fibrovascular pterygium redness by analysing digital images of the pterygium and grading it on a continuous scale of 1 (minimum redness) to 3 (maximum redness). An ocular surface expert graded all 93 images in random order. The reliability of PRGS was determined by comparing pterygium redness measured using the software and by the expert. The mean and standard deviation of redness of the pterygium fibrovascular images measured using PRGS and by the expert were 1.81 ± 0.58 and 1.73 ± 0.61, respectively (P = 0.396). A comparative analysis based on pterygium type showed an increase in redness according to pterygium type (Type I: 1.43 ± 0.32; Type II: 1.67 ± 0.55; and Type III: 2.31 ± 0.46), without significant differences compared to redness measured by the expert (Type I: 1.38 ± 0.34; Type II: 1.78 ± 0.62; and Type III: 2.02 ± 0.66) (all P > 0.05). PRGS could describe and classify pterygia according to their redness, and PRGS-based classification was in agreement with the established classification of pterygia. Therefore, PRGS can be used in addition to the existing pterygium grading system.